Resiliensi Hutan Adat Tenganan Pegringsingan Menghadapi Tekanan Pariwisata dan Regulasi Negara - Fikri Danang Himawan; Pramudya Bumishambara (Department of Political Science, Faculty of Social and Political Science, Udayana University, 2026)
This study analyzes the resilience of Tenganan Pegringsingan Customary Forest against tourism pressure and state regulation. Synthesizing Traditional Ecological Knowledge (TEK), Social Capital, and Ostrom’s Institutional Design, this research employs a qualitative case study to examine the causal-institutional dynamics of resource management. The findings reveal a paradoxical condition: the forest management is internally optimal, supported by high biodiversity and strict customary laws (awig-awig), yet externally vulnerable to legal fragmentation and market commodification. State interventions often create legitimacy crises, while global ecotourism risks eroding sacred values. The study concludes that sustainability requires a